Influence of Ce3+ polarons on grain boundary space-charge in proton conducting Y-doped BaCeO3. Issue 23 (4th June 2018) - Polfus, Jonathan M.; Pishahang, Mehdi; Bredesen, Rune
Abstract : Ce 3+ polarons associated with oxygen vacancies in the grain boundary core lowers the space-charge potential and may enhance n-type conduction. Abstract : Defect segregation and space-charge formation were investigated for a (0 2 1)[1 0 0] symmetric tilt grain boundary in Y-doped BaCeO3 . Density functional theory calculations according to the PBE+ U formalism were used to calculate segregation energies for protons, oxygen vacancies and Y-acceptor dopants from the bulk to the grain boundary core. Defect concentration and potential profiles across the grain boundary were obtained from thermodynamic space-charge models. Oxygen vacancies were found to exhibit a particularly exothermic segregation energy of up to −1.66 eV while protons exhibited segregation energies in the range of −0.47 eV to −0.93 eV. The grain boundary was determined to be predominated by protons below 800 K in 3% H2 O and the corresponding space-charge potential was 0.4–0.7 V under the Mott–Schottky approximation. The role of electronic defects in the space-charge properties was evaluated, and it was substantiated that electron conduction along the grain boundary could become evident under reducing conditions.